2009
DOI: 10.1016/j.jfms.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Field strain feline coronaviruses with small deletions in ORF7b associated with both enteric infection and feline infectious peritonitis

Abstract: Feline coronavirus (FCoV) varies greatly from causing subclinical or mild enteric infections to fatal feline infectious peritonitis (FIP). The open reading frame (ORF) 7b of FCoV has been speculated to play a determining role in virulence as deletions were found to be associated with avirulent viruses. To further clarify the correlation between this gene and FIP, clinical samples from 20 cats that had succumbed to wet-type FIP and 20 clinically healthy FCoV-infected cats were analysed. The ORF7b from the perit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 28 publications
(22 reference statements)
1
35
0
1
Order By: Relevance
“…One FIPV isolate (SFS-01) in the present study had a premature stop codon in the region overlapping 3a, b, another (SFS-11) had a mutation that resulted in an extended 3b protein and no 3c product, and two FIPV isolates had 3 nt and 27 nt deletions in the M protein. The 7a and 7b genes and their products were not studied herein, because isolates of both FECVs and FIPVs with significant mutations have been found to coexist in nature (Kennedy et al, 2001;Lin et al, 2009). Furthermore, deletion of 7b causes FIPVs to become avirulent (Herrewegh et al, 1995).…”
Section: What Is the Mutation That Causes Fecvs To Become Fipvs?mentioning
confidence: 99%
“…One FIPV isolate (SFS-01) in the present study had a premature stop codon in the region overlapping 3a, b, another (SFS-11) had a mutation that resulted in an extended 3b protein and no 3c product, and two FIPV isolates had 3 nt and 27 nt deletions in the M protein. The 7a and 7b genes and their products were not studied herein, because isolates of both FECVs and FIPVs with significant mutations have been found to coexist in nature (Kennedy et al, 2001;Lin et al, 2009). Furthermore, deletion of 7b causes FIPVs to become avirulent (Herrewegh et al, 1995).…”
Section: What Is the Mutation That Causes Fecvs To Become Fipvs?mentioning
confidence: 99%
“…Furthermore, intact 7b genes were described in other field strains of FECV. 52,58 Testing for antibodies directed against the 7b protein was compared against the IFA in one study. The authors showed that the 7b protein assay had high sensitivity but poor specificity, with many false-positive results occurring in uninfected animals.…”
Section: Serologymentioning
confidence: 99%
“…44 The ORF 7b gene was also reported to be truncated in FECV but intact in FIPV strains. 56,57 However, such deletions may not be relevant to biotype since they also can occur with in vitro passage 53 and Lin and colleagues 58 found that small deletions in ORF7b could be found in both biotypes.…”
mentioning
confidence: 99%
“…These deletions may have been acquired during in vitro passaging of the virus as these genes are known to be dispensable for viral replication in cultured cells; actually, during propagation in cell culture FCoV mutants with deletions in the 7b gene are even selected for, suggesting that functional loss of the gene increases viral fitness in vitro (Herrewegh et al, 1995). Of note, avirulent field viruses with (generally small) deletions in gene 7b have been described (Desmarets et al, 2016;Lin et al, 2009a). It is also worrisome that strain 79-1683 thus far is the only serotype II enteric coronavirus isolated.…”
Section: Discussionmentioning
confidence: 99%